Implementation of interdisciplinary relationships in education on the basis of science integration - Gulmira Mailybaeva., Zh.M. Saurykova, Kalibek Ybyraimzhanov, (Opción, 2019)
The article deals with the problem of integrating science into the progressive development of the modern world, connected with the expansion of the scientific discovery scope or coverage of phenomena that are associated with the expansion of the thought space. The development of science and the process of its integration that directly affects the education system in Kazakhstan, are described as a phenomenon that requires the renovation of the curriculum. Researchers provide scientific conclusions on the interdisciplinary relationships in primary education and the ways of its practical implementation. Theoretical and practical aspects of interdisciplinary relationships, proved on a scientific basis are presented.